Identifying and Prioritizing Barriers to Commercializing Researches and Innovations in East Azerbaijan University with AHP Techniques and Providing Appropriate Strategies - Haji Irani, Farhad Nejad; hayak, Kaveh; Asetmal, Eesmail Kholafazade (European Journal of Sustainable Development, 2018)
The purpose of this research is to identify, prioritize the barriers to commercialization of research findings and academic innovations in the eastern province. This research is in terms of survey method and in terms of purpose. Sample size with Cochran formula, 177 out of 330 university staff were selected. Subsequently, the main and secondary criteria were identified. Finally, the main obstacles (individual, structural, cultural, process) and 18 sub-obstacles were identified. Data was analyzed using Hierarchical Analyzer Software (AHP) software, prioritization. The results showed that cultural barriers with the weight of 436 / is the most important barrier and the international exchange of knowledge with the final weight of 191 / barrier is ranked first. Therefore, organizational culture is a major factor and should be strengthened. International exchange of knowledge is possible through easy access to scientific articles and the recruitment of international professors. Key Words: Barriers to Commercialization, Research Findings, Analytical Hierarchy Process (AHP)